Impact of Self-Regulation Skills on Academic Performance of Young Children in Private Schools of Karachi (Journal of Education and Educational Development, 2020)
This research aimed to explore if self-regulation skills had any effect on the academic outcomes of young children in private schools of Karachi, Pakistan. Quantitative research method was used to determine the impact of self-regulation upon the academic outcome of young children by utilizing Early School Self-Regulation Scale-Care Giver Version (Bhamani, 2012).The sample size consisted of randomly chosen 210 children, studying in grades 1 and 2 from seven different private schools in Karachi. The results of the research show that selfregulation skills had a significant impact on the academic outcome of young children in private schools of Karachi, b = -6.3, t (198) = 0.693, p < .01. Self-regulation skills also explained a significant proportion of variance in students grades, R2 = .397, F (1, 198) = 130.536, p < .01.